Beneath a scarlet sky [compact disc, unabridged] : a novel - Sullivan, Mark T. (Brilliance Audio, 2017)
In 1940s Italy, teenager Pino Lella joins an underground railroad helping Jews escape over the Alps, falls for a beautiful widow, and becomes the personal driver of one of the Third Reich's most powerful commanders.